(3CRgGQ GdYQhT aj CNHGQ GdLjhTs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3YHO GdQMef Hf CHj HcQ Hf eMeO GHf SGHb GdOjf GdNVjQj GdSjhWj, LdGd GdOjf,J (B911 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjf EUWai gPG cJGH jSei CRgGQ GdYQhT ai CNHGQ GdLjhT dNUJg ef cJGHi GdeSei QaY TCf GdMHTGf hGddg GdeSJYGf PcQ CUd GdMHT s
(3BNQgG (B:s
(3hbGd GdTgGH GdefUhQi ShOkG MGdcg GdGgGH EPG HOJ JSHi GdfhGXQ hGdbdhH LeGdkG hOJ MSGf GdHjV Cf dh UHQJ ef dhfgG ai cd NO MGdG s
(3HgG fXGe GdJYbjHIs
(3HChdgG Jedc eDQN SfI (B936(3g`s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdJGQjNs